Isolation and characterization of condensed tannin from Acacia mangium willd. and its antibacterial activity - Mohd Hussin, Nasyatul Ekma (2016)
Three experiments have been conducted to extract and evaluate the ability of tannins to bind with proteins and also their inhibition towards the growth of several types of pathogenic skin bacteria. The types of tannins and their molecular weight are believed to be the main factors influencing their activity towards proteins and microbes. In the first experiment, condensed tannin was extracted from several parts of Acacia mangium including leaves, stems, and pods. Sephadex LH-20 was used to separate condensed tannin (CT) from other phenolic compounds contains in the crude extracts. The amount of purified condensed tannin was measured by modified Vanillin-HCl assay method using cathechin as the standard. The concentration of extracted condensed tannin was found to be different in each part. The amount of tannins was calculated based on dry matter (DM) basis. Leaves were found to contain the highest amount which is 3.28% DM, whereas in stems and pods contains 0.98% DM and 1.54% DM, respectively. In second experiment the protein-binding affinity (PBA) of extracted condensed tannins was determined using a protein precipitation assay with bovine serum albumin (BSA) used as the standard proteins. The affinity was measured based on b-value (the b-value represent the quantity of condensed tannin needed to bind half of the maximum precipitable BSA). The average b-value of isolated CT was 0.53 with standard deviation of 0.048. In the third experiment, the antibacterial activity of extracted CT was evaluated. There were three sub-experiment were conducted to evaluate the activity. The first experiment was to measure the zone of inhibition of tested bacteria against 100 mg/mL CT extracts by agar diffusion test. Then, the minimum inhibitory were measured by using microdilution test. Lastly in the third experiment, the log reduction of numbers of bacteria based on time incubation and also by concentration was quantified by time-kill assay. From the study, it showed that all tested bacterium were susceptible to the CT at the concentration of 100 mg/mL, with diameter zone of inhibition of ranged between 12.0 to 13.0 mm. However, the minimum inhibitory concentrations (MIC) were different between the isolates. Compared to resistant strains, S. aureus ATCC 29213 was found to be inhibited by CT extract at low concentration (1 mg/mL) and it also was killed after 6 hours exposure with 10 mg/mL CT extracts. On the other hand, all the MRSA isolates had varied inhibitory effects. The MIC values were in the range of 2 mg/mL to 10 mg/mL and most of the isolates were inhibited at 5 mg/mL. Based on the collected data it shows that condensed tannins had the higher content in A. mangium leaves. Eventhough, the amount were lower in stems and pods, their affinity to bind protein were almost similar. These compounds also shows a good antibacterial effects against S. aureus (including resistant strains).